Computing NodeTrix Representations of Clustered Graphs - Da Lozzo, Giordano; Di Battista, Giuseppe; Frati, Fabrizio; Patrignani, Maurizio (Journal of Graph Algorithms and Applications, 2018)
NodeTrix representations are a popular way to visualize clustered graphs; they represent clusters as adjacency matrices and inter-cluster edges as curves connecting the matrix boundaries. We study the complexity of constructing NodeTrix representations focusing on planarity testing problems, and we show several NP-completeness results and some polynomial-time algorithms. Building on such algorithms we develop a JavaScript library for NodeTrix representations aimed at reducing the crossings between edges incident to the same matrix.